Deduction and Application of the Average Switch Model in Power Electronic Devices for Simulation Time Reduction - Benavides-Córdoba, Santiago; Romero-Carvajal, Anamaría; Muñoz-Galeano, Nicolas; Cano-Quintero, Juan Bernardo; López-Lezama, Jesús María (Ingeniería, 2024)
Context: Time is a crucial issue in the simulation of power electronics (PE) devices, even more when these elements are integrated into microgrids. Method: This paper deals with the deduction of the average switch model for PE devices with the purpose of reducing simulation times. For doing this, the average model is only applied over the power switches of PE devices, not being applied over the complete topology as traditionally done. The proposed average model switch permits eliminating the ripple of voltage and currents but keeping the transient of the signals. The average model switch is derived for Boost and Buck converter switches and then generalized to power inverter switches. The proposed approach is validated using OpenModelica software. Results: A system featuring a battery, a DC/DC converter, and an inverter connected to the power grid was simulated. A comparison was performed between a simulation that considers the power switches and a simulation that uses the proposed average model switch, the time simulation was reduced up to 99.788 %, which validates the proposed approach. Conclusions: The proposed average switch model significantly reduces simulation times. This method offers a promising way to streamline power electronics device simulations, particularly in the context of microgrids and other applications where time efficiency is critical.